Qualitative and quantitative phytochemical analysis and in-vitro biological activity of Rheum ribes L. different parts - (:unkn) unknown (ISTANBUL UNIV, FAC PHARMACY, 2019)
The methanol extracts from different parts of Rheum ribes were subjected to qualitative and quantitative phytochemical and in vitro biological activity (antioxidant, anti-urease, anticholinesterase). Qualitative phytochemical tests were performed using standard analysis methods and these studies revealed the presence of phenolics and tannins. Following this, a quantitative determination of total phenolics and tannins contents was carried out. The antioxidant activity of the extracts were assayed using DPPH, FRAP TEAC/ABTS and CUPRAC techniques. In addition, the anti-urease and anticholinesterase activity of the extracts were examined using indophenol and Ellman methods, respectively. In this study, it was determined that the macerated flowers extract contained higher total phenolic and tannins contents than the other extracts. According to the results obtained from the antioxidant experiment, the macerated extract of flowers showed the strongest ABTS.+ scavenging and ferric reducing antioxidant power activity. The macerated leaves and Soxhlet radix extracts exhibited the strongest DPPH. scavenging and cupric reducing antioxidant activity, respectively. The young shoots extracts obtained using the Soxhlet methods showed the highest anticholinesterase activity. All extracts obtained from different parts of the plant were found to have very low anti-urease activity when compared to the anti-urease activity of standard compound. Therefore, methanol extracts from plant's flowers, leaves and young shoots can be used as a natural antioxidant and anticholinesterase agent respectively, for the pharmaceutical and food industry in the future.
Keywords: Rheum ribes; antioxidant; anti-uresae; anticholinesterase; phytochemical analysis; ANTIOXIDANT ACTIVITY; EXTRACT; METHANOL; PLANTS; POWER